Arkais dalam Bahasa Melayu Daerah Seberang Kota Jambi: Tinjauan Deskriptif - Yudi Fahriyan (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2017)
ABSTRACT The purpose of this study is to describe the form, meaning, and use of ancient Malay language in the area of ​​Seberang Jambi with descriptive reviews. The scope of this study discusses the form, meaning, and use of Malay archipelago language Jambi. The location of this research is across Seberang Jambi city. The data in this research is native speakers of Malay Seberang Jambi city. Data analysis techniques in this study using extralingual and intalingual methods. In terms of ancient word form in Malay Seberang city of Jambi in its use have affiksinya process, namely additio prefix, suffix, and confix. Keywords : archaic, Malay language Seberang of Jambi city